Rapid synthesis of Pt-based alloy/carbon nanotube catalysts for a direct methanol fuel cell using flash light irradiation - Park, Sung-Hyeon; Jung, Hye-Mi; Um, Sukkee; Song, Yong-Won; Kim, Hak-Sung (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
We synthesized Pt, Pt-Ru alloy and Pt-Ru-Mo alloy nanoparticles on the multi-walled carbon nanotubes (MWCNTs) using flash light irradiation and characterized these catalysts. Pt-100, Pt-50-Ru-50 alloy and Pt-43-Ru-43-Mo-14 alloy are coated onto MV/CNTs followed by flash light irradiation to facilitate the formation of nanoparticle-alloys. The fabricated pure Pt and Pt-based alloy nanoparticle/MWCNTs were characterized by X-ray diffraction (XRD), raman spectroscopy and scanning electron microscopy (SEM). Cyclic voltammetry (CV) studies and electrochemical impedance spectroscopy (EIS) results revealed that the Pt-43-Ru-43-Mo-14/MWCNT catalyst has higher activity and stability with regard to methanol electro-oxidation than the Pt-100/MWCNT and Pt-50-Ru-50/MWCNT catalysts. Copyright (C) 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CARBON NANOTUBES; SUPPORTED PLATINUM; ANODE CATALYST; ELECTROOXIDATION; ELECTROCATALYSTS; NANOPARTICLES; PERFORMANCE; ALLOY; METAL; SPECTROSCOPY